2014
DOI: 10.1179/1743294414y.0000000278
|View full text |Cite
|
Sign up to set email alerts
|

Stirring effects on aluminium coatings electrodeposited in ionic liquids

Abstract: Aluminium coatings were electrodeposited on Fe9Cr1Mo steel from AICI3-1-ethyl-3-methyl imidazolium chloride ionic liquid at room temperature and the effect of solution stirring on deposition rate, preferred crystal orientation, surface morphology and roughness have been investigated. Aluminium coating could not be obtained in the unstirred solution for a deposition current density of 20 mA cm-2 or higher. However, vigorous stirring of the bath enabled the deposition at a current density of 20 mA cm-2 or higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…The phase determination of the synthetic products was carried out through powder X-ray diffraction (XRD), performed using a XR D Bruker D8 Advance powder diffractometer employing Cu Kα (1.54187 Å) radiation in the 2θ range 36-80°, applying a step size of 0.022° 2θ and a step counting time of 0.27 s. Deconvultion of the peaks in the powder scan have been performed by means of the single line profile analysis [14], involving the fitting of the peaks with 2 Voigt functions (one for the K and for K). Voigt function is a convolution of a Lorentzian and a Gaussian functions.…”
Section: Xrd Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The phase determination of the synthetic products was carried out through powder X-ray diffraction (XRD), performed using a XR D Bruker D8 Advance powder diffractometer employing Cu Kα (1.54187 Å) radiation in the 2θ range 36-80°, applying a step size of 0.022° 2θ and a step counting time of 0.27 s. Deconvultion of the peaks in the powder scan have been performed by means of the single line profile analysis [14], involving the fitting of the peaks with 2 Voigt functions (one for the K and for K). Voigt function is a convolution of a Lorentzian and a Gaussian functions.…”
Section: Xrd Analysismentioning
confidence: 99%
“…Gaussian width is related to the average strain of the crystallite while the Lorentzian width is related to the crystallite size. [14] On this background, it is possible to retrieve information on the effect of the experimental conditions on the strain and size of the crystals as well as the texture coefficient. The texture coefficient is defined in equation (2):…”
Section: Xrd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For such purpose, the anticorrosion ability of the Al-coatings is utilized [ 22 ], requiring the formation of a homogeneous and crack-free layer [ 23 ]. To achieve such quality, the effects of various deposition parameters have been evaluated, such as the composition of the ionic liquids [ 24 , 25 , 26 ], deposition current [ 27 , 28 , 29 ], electrolyte temperature [ 19 ], solution stirring [ 30 ] and sonication [ 31 ]. The usage of several additives has also been proposed [ 32 ] to achieve smooth and thick aluminium coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Electrodeposition in stirred solution has the advantage of reducing the thickness of the diffusion layer, thereby improving the deposition rate and the homogeneity of the deposit. However, even though some studies investigated the effect of temperature [ 12 , 15 , 16 ], very little work was reported on the effect of solution stirring [ 17 , 18 ] and, to the best of our knowledge, no one has addressed the effect of sonication so far.…”
Section: Introductionmentioning
confidence: 99%